The Designing of Promotional Video about Outdoor Tourism Destinations in Subdistrict of Balasklumprik - Pangestu, Rafi (BARIK, 2025)
The Subdistrict of Balasklumprik is a subdistrict located in the District of Wiyung, Surabaya City. In this subdistrict, there are five tourist attractions, those are Balasklumprik City Park, Wisata Batas Kampung, Grand Harvest Park, Balasklumprik Food Court, and Pondok Maritim Food Court. The design of promotional video need to be done because according to the result of questionnaire, there are still a lot of respondents whose know, but not yet visited those tourist attractions. And as an effort to increase visitors for those tourist attractions. So hopefully if the promotional video has been made, then the audience can be persuaded to visit the tourist attractions in Balasklumprik. The concept of the promotional video are synopsis, storyline, and storyboard. The process of making the video are video recording, video editing, and then video rendering. The result of making the video are, a finished video is uploaded into YouTube and its link was shared into social media of Instagram and Whatsapp.